INOVASI PENINGKATAN PENYIMPANAN ARSIP MELALUI APLIKASI SAVE ARCHIVE DI BADAN KESATUAN BANGSA DAN POLITIK (BAKESBANGPOL) KABUPATEN KEDIRI - Alfina Fajrin Fauziah; Trenda Aktiva Oktariyanda (Universitas Negeri Surabaya, 2022)
Archival maintenance in Bakesbangpol Kediri Regency is still low, this can be seen from the number of archives that are not maintained. The volume of archives that are increasing every day is not followed by a good shrinkage process, resulting in uncontrolled archive volumes. The innovation launched by Bakesbangpol Kediri Regency, is the Save Archive Application, to optimize archive management administration services as well as to answer problems related to archival implementation at Bakesbangpol Kediri Regency, so that it can give birth to reliable archive management innovations. The purpose of this study is to describe the Save Archive application. The type of research chosen by the researcher is descriptive research with a qualitative approach, with data collection through observation, interviews, documentation, and literature study. The results show that the innovation of the Save Archive application has worked well in accordance with the foundation used, namely the Government Regulation of the Republic of Indonesia Number 28 of 2012 concerning the Implementation of Law no. 43 of 2009 concerning Archives and Regulation of the Minister of Empowerment of State Apparatus and Bureaucratic Reform Number 11 of 2015 concerning Roadmap of 2015-2019 Bureaucratic Reform. Sources of Innovation Ideas get input from employees. The culture of innovation in the innovation of the Save Archive application is archive management that prioritizes ease of storage, retrieval and efficiency control of archives. Furthermore, the capabilities and innovation tools of the Save Archive application are adequate, but there is a lack of special employees for archive managers or archivists. Then the goals, results, drivers and obstacles are to facilitate the process of storing and recovering archives, as well as optimizing archive maintenance, the obstacle is that there are occasional errors and downs on the network. Finally, Bakesbangpol Kediri Regency can optimize archive management administrative services that ensure the level of archive security. Keywords: Administrative Services, Archive Management Innovation, Save Archive.